Identification and Modelling of Religious Tourism Supply Chain Enablers in Post-Covid Era Using ISM - Dr Parul Sinha; Dr Rajkumari Mittal (ASEAN Journal on Hospitality and Tourism, 2021)
Post-Covid-19 pandemic, the supply chains of all the trades faced a setback, but the tourism sector faced an extended jolt of this disaster. Religious tourism, which has been adding a sizeable revenue to Indian GDP, came to a downfall. This manuscript aims to identify and model the enablers of the religious tourism supply chain for reviving the economy in the post-Covid era. The research paper elucidates that post-shock of Covid-19, understanding religious tourism enablers will provide opportunities to all the stakeholders of this chain. Eleven enablers for the religious tourism supply chain were identified. The modelling of these enablers using ISM (Interpretive Structural Modelling), provides insight into their hierarchy and interdependence upon each other. The ISM model also illustrates that the enabler Pilgrims belief and value, a mandatory obligation is the most crucial enabler and influence all other enablers. Religious tourism supply chain stakeholders can employ this model to formulate strategies to overcome the post-pandemic challenges. Subsequently focusing upon the key enablers essential in reviving the tourism sector economy.